Numerical Modeling of Gas Hydrate Recycling in Complex Media: Implications for Gas Migration Through Strongly Anisotropic Layers. Issue 11 (23rd November 2022) - Peiraviminaei, A.; Gupta, S.; Wohlmuth, B.
Abstract: Burial driven recycling is an important process in the natural gas hydrate (GH) systems worldwide, characterized by complex multiphysics interactions like gas migration through an evolving gas hydrate stability zone (GHSZ), competing gas‐water‐hydrate (i.e., fluid‐fluid‐solid) phase transitions, locally appearing and disappearing phases, and evolving sediment properties (e.g., permeability, reaction surface area, and capillary entry pressure). Such a recycling process is typically studied in homogeneous or layered sediments. However, there is mounting evidence that structural heterogeneity and anisotropy linked to normal and inclined fault systems or anomalous sediment layers have a strong impact on the GH dynamics. Here, we consider the impacts of such a structurally complex media on the recycling process. To capture the properties of the anomalous layers accurately, we introduce a fully mass conservative, high‐order, discontinuous Galerkin (DG) finite element based numerical scheme. Moreover, to handle the rapidly switching thermodynamic phase states robustly, we cast the problem of phase transitions as a set of variational inequalities, and combine our DG discretization scheme with a semi‐smooth Newton solver. Here, we present our new simulator, and demonstrate using synthetic geological scenarios, (a) how the presence of an anomalous high‐permeability layer, like a fracture or brecciated sediment, can alter the recycling process through flow‐localization, and more importantly, (b) how an incorrect or incomplete approximation of the properties of such a layer can lead to large errors in the overall prediction of the recycling process. Plain Language Summary: Gas hydrates are complex geosystems characterized by highly coupled multiphysics processes. Natural gas hydrates play an important role in the global carbon cycle and are also seen as a potential energy resource. A key question is how and where they form in nature, and how much hydrate there is in the world today. One of the common processes responsible for their formation is the burial driven recycling, where sedimentation continuously buries the GH layer and upward migrating free gas below the GHSZ, leading to distinct GH layers with high saturation in the vicinity of the base of the GHSZ. Simulation of the GH recycling process has many numerical challenges like solid‐fluid and fluid‐fluid phase transitions, rapidly switching phase states, appearing and disappearing phases, evolving sediment properties, and highly complex structure of the geological subsurface. In this manuscript, we particularly focus on the complex subsurface structure. We present a numerical scheme based on the DG finite element method which can handle full material anisotropies. Our results show that the presence of strongly anisotropic material anomalies (like faults) leads to a focused chimney like gas flow path, and an incorrect handling of such material anomalies can lead to completely different dynamical behavior. Key Points: Structural heterogeneity linked to inclined fault systems or anomalous sediment layers have a strong impact on the gas hydrate dynamics The presence of anomalous high‐permeability layers within gas hydrate stability zone alters the recycling process through flow‐localization The presented discontinuous Galerkin scheme is able to accurately capture the gas hydrate recycling processes through strongly anisotropic materials